Hybrid Bioprinting of Chondrogenically Induced Human Mesenchymal Stem Cell Spheroids - De Moor, Lise; Fernandez, Sélina; Vercruysse, Chris; Tytgat, Liesbeth; Asadian, Mahtab; De Geyter, Nathalie; Van Vlierberghe, Sandra; Dubruel, Peter; Declercq, Heidi (Frontiers in Bioengineering and Biotechnology, 2020)
To date, the treatment of articular cartilage lesions remains challenging. A promising strategy for the development of new regenerative therapies is hybrid bioprinting, combining the principles of developmental biology, biomaterial science, and 3D bioprinting. In this approach, scaffold-free cartilage microtissues with small diameters are used as building blocks, combined with a photo-crosslinkable hydrogel and subsequently bioprinted. Spheroids of human bone marrow-derived mesenchymal stem cells (hBM-MSC) are created using a high-throughput microwell system and chondrogenic differentiation is induced during 42 days by applying chondrogenic culture medium and low oxygen tension (5%). Stable and homogeneous cartilage spheroids with a mean diameter of 116 ± 2.80 μm, which is compatible with bioprinting, were created after 14 days of culture and a glycosaminoglycans (GAG)- and collagen II-positive extracellular matrix (ECM) was observed. Spheroids were able to assemble at random into a macrotissue, driven by developmental biology tissue fusion processes, and after 72 h of culture, a compact macrotissue was formed. In a directed assembly approach, spheroids were assembled with high spatial control using the bio-ink based extrusion bioprinting approach. Therefore, 14-day spheroids were combined with a photo-crosslinkable methacrylamide-modified gelatin (gelMA) as viscous printing medium to ensure shape fidelity of the printed construct. The photo-initiators Irgacure 2959 and Li-TPO-L were evaluated by assessing their effect on bio-ink properties and the chondrogenic phenotype. The encapsulation in gelMA resulted in further chondrogenic maturation observed by an increased production of GAG and a reduction of collagen I. Moreover, the use of Li-TPO-L lead to constructs with lower stiffness which induced a decrease of collagen I and an increase in GAG and collagen II production. After 3D bioprinting, spheroids remained viable and the cartilage phenotype was maintained. Our findings demonstrate that hBM-MSC spheroids are able to differentiate into cartilage microtissues and display a geometry compatible with 3D bioprinting. Furthermore, for hybrid bioprinting of these spheroids, gelMA is a promising material as it exhibits favorable properties in terms of printability and it supports the viability and chondrogenic phenotype of hBM-MSC microtissues. Moreover, it was shown that a lower hydrogel stiffness enhances further chondrogenic maturation after bioprinting.